Macroeconomic Variables, Demographic Factors and Current Account Balance in Nigeria: A Causal Relationship - Soliu Bidemi Adegboyega; Olukayode Emmanuel Maku; Kehinde Kabir Agbatogun (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
This paper examines the effect of macroeconomic variables, demographic factors toward current account balance in Nigeria. It analyzed the connection between each of domestic savings and investment on current account balance by examining the role and direction of the selected demographic variables. The Toda-Yamamoto approach to causality was used to analyze the study. The result shows that the direction of causality was from both domestic saving and investment to current account balance. However, there is no reverse causation from the current account balance to domestic saving and investment. Thus, the selected demographic variables had no significant causation towards current account balance, investment, and domestic saving. The government needs to finance the desired investment through increased domestic saving without undue reliance on foreign resources